2012
DOI: 10.1017/s0272263112000137
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Prosodic Cues in Learning New Words in an Unfamiliar Language

Abstract: The artificial language learning paradigm was used to investigate to what extent the use of prosodic features is universally applicable or specifically language driven in learning an unfamiliar language, and how nonnative prosodic patterns can be learned. Listeners of unrelated languages—Dutch (n= 100) and Korean (n= 100)—participated. The words to be learned varied with prosodic cues: no prosody, fundamental frequency (F0) rise in initial and final position, final lengthening, and final lengthening plus F0 ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 58 publications
9
60
0
Order By: Relevance
“…Local cues are exploited by listeners in artificial language learning tasks as well: Tyler & Cutler (2009) have shown that English, French and Dutch speakers use lengthening as a cue to phrase-finality and this helps them detect upcoming word onsets. Kim et al (2012) report similar results with speakers of Dutch and Korean.…”
Section: A Prosodic Cues To Word Boundariessupporting
confidence: 76%
“…Local cues are exploited by listeners in artificial language learning tasks as well: Tyler & Cutler (2009) have shown that English, French and Dutch speakers use lengthening as a cue to phrase-finality and this helps them detect upcoming word onsets. Kim et al (2012) report similar results with speakers of Dutch and Korean.…”
Section: A Prosodic Cues To Word Boundariessupporting
confidence: 76%
“…In particular, as discussed in the introduction, the fact that Korean listeners perceive (phonetically poorer) unreleased stops better than (phonetically richer) released stops in processing non-native speech has provided a concrete example of a situation where phonological experience overrides phonetic richness in non-native speech perception (Cho & McQueen, 2006). The language-specificity of speech perception has also been observed in lexical segmentation of unfamiliar artificial languages or non-native languages-e.g., the use of language-specific phonotactics (Weber & Cutler, 2006) and rhythmic/prosodic cues (Cutler & Otake, 1994;Kim et al, 2012;Tyler & Cutler, 2009) in processing non-native speech. The results of the present study therefore appear to be in contrast to the generally observed dependency that listeners have on their phonological knowledge in the perception of unfamiliar or non-native speech.…”
Section: Discussionmentioning
confidence: 99%
“…Listeners had to identify the words in the test phase. This paradigm has been shown to be effective in testing effects of specific cues in the speech signal without recourse to any prior lexical knowledge and it has also revealed listeners' use of native segmentation cues in lexical segmentation of these unfamiliar, non-native languages (e.g., Bagou et al, 2002;Kim et al, 2012;Saffran et al, 1996;Tyler & Cutler, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations